'Living with intimate partner violence' A literature review of pregnant women's experiences. - Panda, Sunita (My University, 2017)
Pregnancy brings joy to most women’s lives. However, some women do not enjoy their pregnancy, due to physical and/or emotional health problems, or social circumstances such as being in a relationship characterised by intimate partner violence (IPV). The aim of this review is to explore women’s experiences of pregnancy and being in a relationship with IPV. The electronic databases PubMed, CINAHL, PsycINFO and Web of Science were searched in June 2015 for related qualitative studies. Twelve studies, including 157 participants, were identified and included in this review. Four themes emerged from the data: 1) Feeling trapped/fear around disclosure and uncertainty, 2) Adapting and changing, 3) Protecting the unborn and 4) Hope and faith. In order to provide support to these women, midwives need to know how to identify women living with IPV, and how to help them through information and formal social support networks.
PUBLISHED
Keywords: Intimate partner violence; Health